Analisis Manajemen Strategis Dan Manajemen Risiko Terhadap Bank Mandiri Syariah - Shella Angelica Valentine (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to analyze the implementation of strategic management and risk management at Bank Mandiri Syariah (BMS) and its impact on the bank's performance and stability. This research adopts a qualitative approach by utilizing data from previous studies related to the research topic. The findings of this study indicate that BMS has implemented strong risk management practices, including risk identification, measurement, monitoring, and control. Additionally, strategic management plays a role in determining the direction of the bank and ensuring compliance with Sharia principles. The study concludes that the integration of strategic management and risk management is crucial for BMS to maintain its competitiveness and sustain growth in the dynamic Islamic banking industry.